Colorectal Cancer Immunotherapy: Options and Strategies - Johdi, Nor Adzimah; Sukor, Nur Fazilah (Frontiers in Immunology, 2020)
Colorectal cancer is the third most common cancer in the world with increasing incidence and mortality rates globally. Standard treatments for colorectal cancer have always been surgery, chemotherapy and radiotherapy which may be used in combination to treat patients. However, these treatments have many side effects due to their non-specificity and cytotoxicity towards any cells including normal cells that are growing and dividing. Furthermore, many patients succumb to relapse even after a series of treatments. Thus, is it crucial to have more alternative and effective treatments to treat CRC patients. Immunotherapy is one of the new alternatives in cancer treatment. The strategy is to utilize patients’ own immune system in combating the cancer cells. Cancer immunotherapy overcomes the issue of specificity which is the major problem in chemotherapy and radiotherapy. The normal cells with no cancer antigen are not affected. The outcome of some cancer immunotherapy have been astonishing in some cases but some are not, which rely on the status of patients’ own immune system. Those patients who responded well to cancer immunotherapy, have a better prognostic and better quality of life.